EMPLOYEE EMPOWERMENT ON ORGANIZATIONAL COMMITMENT IN BANK INDONESIA REPRESENTATIVE IN NORTH SULAWESI - Hutagaol, Intan Magdalena (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Employee empowerment is the most promising concept related with human resources condition nowadays that demanded qualified and competent people. By having empowerment strategy, employees in middle level management are given extra responsibility and authority on their own job without pressure from top level management in order to increase their commitment towards organization. The objective of this study is to analyze the impact of employee empowerment on organizational commitment in Bank Indonesia Representatives in North Sulawesi. The method used in this research is descriptive with qualitative approach. The sample of this research is employees in middle level management who empower and be empowered as many as 8 informants using purposive sampling technique. The results based on data collection method processed using the In-Depth Interview. In the findings, there is significant impact of employee empowerment on organizational commitment, especially in normative dimension. It is because the implemented empowerment strategy such as training, education, motivation and reward system at Bank Indonesia require employee to increase their sense of self-determination and self-efficacy to be responsible toward assigned task. This research suggests to Bank Indonesia Representatives in North Sulawesi to maintain the empowerment strategy and to increase the affective commitment of employee on institution. Â  Keywords: human resources, empowerment, commitment